2023
DOI: 10.3390/jcm12041298
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-Associated Pneumonia in COVID-19 Patients Admitted in Intensive Care Units: Relapse, Therapeutic Failure and Attributable Mortality—A Multicentric Observational Study from the OutcomeRea Network

Abstract: Introduction: Ventilator-associated pneumonia (VAP) incidence is high among critically ill COVID-19 patients. Its attributable mortality remains underestimated, especially for unresolved episodes. Indeed, the impact of therapeutic failures and the determinants that potentially affect mortality are poorly evaluated. We assessed the prognosis of VAP in severe COVID-19 cases and the impact of relapse, superinfection, and treatment failure on 60-day mortality. Methods: We evaluated the incidence of VAP in a multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…In fact, VAP is the most important nosocomial infection we have faced during the pandemics. In a retrospective analysis of mechanically ventilated SARS-CoV-2 ARF in France, Moreno et al reported an incidence of more than 50% [ 8 ], which is consistent with the findings of the French multicenter OUTCOME-REA group and a systematic literature review [ 9 ]. All studies reported a high risk of VAP, mainly occurring late during mechanical ventilation, due to Staphylococcus aureus, non-fermentative Gram-negative bacteria, and multidrug-resistant Enterobacterales.…”
Section: Impact Of Sars-cov-2 Pandemics On the Risk Of Nosocomial Inf...supporting
confidence: 74%
See 1 more Smart Citation
“…In fact, VAP is the most important nosocomial infection we have faced during the pandemics. In a retrospective analysis of mechanically ventilated SARS-CoV-2 ARF in France, Moreno et al reported an incidence of more than 50% [ 8 ], which is consistent with the findings of the French multicenter OUTCOME-REA group and a systematic literature review [ 9 ]. All studies reported a high risk of VAP, mainly occurring late during mechanical ventilation, due to Staphylococcus aureus, non-fermentative Gram-negative bacteria, and multidrug-resistant Enterobacterales.…”
Section: Impact Of Sars-cov-2 Pandemics On the Risk Of Nosocomial Inf...supporting
confidence: 74%
“…All studies reported a high risk of VAP, mainly occurring late during mechanical ventilation, due to Staphylococcus aureus, non-fermentative Gram-negative bacteria, and multidrug-resistant Enterobacterales. VAP occurred in the most severe patients, who were more likely to receive corticosteroids, and is associated with low viral clearance [ 8 , 9 , 10 ].…”
Section: Impact Of Sars-cov-2 Pandemics On the Risk Of Nosocomial Inf...mentioning
confidence: 99%
“…In the same vein, Pałka et al 29 demonstrated high prevalence of XDR organisms of 22.6% in the intensive care unit (ICU) and 14.8% in non-ICUs among all isolate especially XDR- A. baumannii . Increasing MDR post COIVD-19 might be linked to human factors including delayed care, increasing device usage, and inappropriate use of antibiotics in the trial of treat the complications of COVID-19 pandemic 3 , 30 . The disparity in the distribution of MDR and XDR in Egypt before and after the pandemic could be attributed to the different AMR response plans in each governorate, highlighting the importance of developing a national AMR response plan for Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of relapse could be partially explained by the proportion of patients with SARS-CoV-2 acute respiratory failure and VAP. Relapses and superinfections were more frequently seen in those particular patients, with identified risk factors, such as being treated for non-fermentative GNB infections, requiring ECMO, and being treated with other broad-spectrum antimicrobials [ 41 ]. Despite acceptable plasma trough level, concentration obtained in the alveolar fluid may have been insufficient to eradicate the high inoculum of DTR non-fermentative GNB recovered from VAP episodes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%